Measuring trust in institutions and its causal effect - Stefan P. Penczynski; Maria Isabel Santana (Quantitative Economics, 2024)
We propose a novel way of measuring trust in institutions, which draws on the experimental method used to elicit time preferences. Our measure is provided in the meaningful metric of the subjective probability of trustworthiness of the trustee. In a lab-in-the-field setting in the Philippines, we measure trust in two different financial institutions. Additionally, we exploit exogenous variation in the eligibility for a future payment to examine whether a promise fulfilled by the institution increases trust and changes individual financial behavior. We find that eligible individuals significantly increase savings held with the institution.
http://dx.doi.org/10.5281/zenodo.8199884
Keywords: C91; D81; D90; O10; 330; Trust; institutions; experiment; time preference; risk preference; savings